Arabic Manuscripts in Islamic Historiography during the Mamluk Dynasty - Safari Safari (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Historiography of Islam has often reflected the efforts to construct history distorted by political elements of power and the subjective interests of historians, hindering the presentation of the true historical facts. One of the pressing issues is how the use of the Arabic language in historical texts influences the understanding of Islamic historiography. This research aims to detail and analyze the characteristics of Islamic historiography during the medieval period, especially in the context of the Mamluk Dynasty, with a focus on the role of the Arabic language. The research methodology involves a literature review, examining various previous studies on Islamic historiography. The results of data analysis reveal characteristics of encyclopedic scholarship, the pivotal role of the Arabic language as the primary means of communication in constructing historical narratives, and the presence of creativity and originality in historical writings. Thus, this research makes a significant contribution to the development of theoretical frameworks for understanding the history of medieval Islam during the Mamluk period. This study is essential for delving into Islamic historiography of the past, especially in the context of the use of the Arabic language, to gain a deeper understanding of how Islamic history was recorded and conveyed during the Mamluk Dynasty. With this understanding, we can grasp the political, cultural, and social nuances that shaped the Islamic historical narrative during this period, while highlighting the crucial role of the Arabic language in this process.